Periaortic lymphoma in a cat. Issue 2 (September 2017) - Bree, Laura; Bergamino, Chiara; Mullins, Ronan; Kelly, Pamela; Shiel, Robert
Case summary: A 14-year-old neutered male Siamese cat was presented with a 3 month history of lethargy, inappetence, dehydration, hindlimb ataxia and intermittent proprioceptive deficits in the hindlimbs. Physical examination revealed low body condition score (1.75/5), pallor and bilateral basilar grade II/VI systolic heart murmur. Neurological examination revealed hindlimb ataxia, severe atrophy of the hindlimb musculature, intermittent hindlimb proprioceptive deficits and normoreflexia. Clinicopathological investigations revealed non-regenerative anaemia (haematocrit 0.17 l/l; reference interval [RI] 0.24–0.45 l/l) and increased feline pancreatic lipase concentration (Spec fPL test [IDEXX] 8.3 μg/l; RI 0.1–3.5 μg/l). Feline leukaemia virus antigen and feline immunodeficiency virus antibody tests were negative. Thoracic and abdominal imaging revealed a soft tissue structure in the area of the thoracoabdominal aorta. CT confirmed a periaortic contrast-enhancing mass extending from the level of T9–L2, with associated intervertebral infiltration at the level of T11–T12. Post-mortem examination confirmed the presence of a solid, white, multinodular, well-demarcated mass encircling the aorta extending from T9–L2. Based on histopathology and immunohistochemistry, a diagnosis of B-cell lymphoma was made. Lymphoma was also identified histopathologically within the kidneys and spleen. Evidence of mild Wallerian degeneration was present within the spinal cord, indicating compression at the level of the periaortic mass. Relevance and novel information: To our knowledge, this is the first report of periaortic lymphoma in the cat. Although periaortic tumours are exceptionally rare in veterinary medicine, lymphoma should be considered as a differential in cats.